Otimização da eficiência luminosa através da substituição de sistema de lâmpadas de uma unidade fabril do norte do Paraná - Souza, Ailton de (2014)
This paper presents a strategic proposal in the energy area regarding the consumption of electrical energy in a company located in northern Paraná, which owns warehouses in stock with high tariff consumption, presenting as filler installed mostly lighting type HO fluorescent lamps ("High output "). There was a study of applicability of replacing current lighting system with LED lamps showing the benefits of this lighting system compared to existing systems, addressing cost benefit, energy efficiency, tariff system and a summary of the technology used in lamps. This paper shows a model shed that was used as a prototype of the proposal, showing the benefits of lighting when used LED lamps.